Modelling spatial-temporal changes in carbon sequestration by mangroves in an urban coastal landscape. (5th October 2022) - Rosa, Lorena N.; Duarte de Paula Costa, Micheli; de Freitas, Débora M.
Abstract: Mangrove deforestation by land use conversions is the greatest threat to the conservation of coastal ecosystems, ranking Brazil as a country with high gross annual CO2 emissions. Despite the recognized socio-ecological importance in providing essential ecosystem services (e.g., erosion prevention, protection against extreme weather events, provision of habitats for estuarine species, and blue carbon storage), mangroves have been converted from blue carbon sinks to sources. Here, we modelled and evaluated the spatial-temporal changes in blue carbon stocks and net sequestration potential in mangrove forests in Santos and São Vicente, Brazil, from 1988 to 2050. We used classified images obtained from MapBiomas and the InVEST Coastal Blue Carbon model, which quantifies the potential carbon sequestered in the study area based on changes in the land use and land cover over the determined study period. We found an increased trend in carbon stocks and net sequestration of mangroves in both municipalities. Over the analysis period, carbon stocks in the mangroves of the city of Santos increased 29% in total, while we found a smaller rise (14%) in São Vicente. We found that land use changed substantially during 1988 until 2018, with mangrove extent varying in the region from 3, 375 ha in 1988 to 3, 764 ha in 2018 within the entire study region. Overall, the net carbon sequestration was approximately 925, 393 Mg CO2 e and 287, 130 Mg CO2 e, in Santos and São Vicente, respectively, over a period from 1988 to 2050. To our knowledge, this study is the first to quantify soil carbon stock and accumulation in mangroves along an urban coastal landscape in Brazil and emphasizes the current and future role of mangroves in climate change mitigation. Our findings can support the development of public policies for mangrove conservation and restoration actions to mitigate climate impacts. Highlights: Land conversion is the main cause of mangrove deforestation in urban areas. Net carbon sequestration has increased 29% and 14% in Santos and São Vicente. Mangrove extent in the region varied from 3, 375 ha in 1988 to 3, 764 ha in 2018. Net carbon sequestration may be as high as 925, 393 Mg CO2 e over 62 years.